REDISCOVERING ARCHAEOLOGY USING THE CULTURAL HERITAGE OF SERANG CITY, BANTEN PROVINCE FOR COMMUNITY RECOVERY DURING COVID-19 PANDEMIC - Akbar, Ali (International Review of Humanities Studies, 2021)
Many archaeological researches have been conducted in Serang City, Banten Province for decades so that a significant amount of knowledge has been produced. The Public Archaeology approach, especially museums and cultural resource management, has also been applied. However, these efforts have not been maximized resulting in several problems. Particularly, since 2020, COVID-19 pandemic has affected various fields and sectors, including the cultural sectors related to the preservation and management of cultural heritage in Serang City. The efforts to prevent the transmission of COVID-19 have been carried out by implementing health protocols and large-scale social restriction policies including on the sites and museums. The pandemic along with its uncertainty opens the potential for some problems to increasingly influence the social and political aspects; for instance, the income of the local community has decreased. Thus, a new approach known as Rediscovering Archaeology is needed to reduce the existing problems. This approach is carried out by conducting a research followed by a community service involving multidisciplinary knowledge and several related parties or Penta Helix. The methods include field observation, interviews, and ongoing mentoring. This approach has been shown to reduce the potential social and political tensions in society. This approach also convinces related parties that archaeological heritage can be a cultural capital in dealing with the pandemic and is expected to generate prosperity for the community in the future.